Pembangunan Papan Pelatih 8051 Pelbagai Aplikasi - Yusof, Mohd Fadhli (Universiti Sains Malaysia, 2006)
The development of 8051 trainer with many application is a project that use a new innovation of MCS51 microcontroller produced by Atmel, this system use In System Programmable internal or external flash memory. In System Programmable means that the microcontroller itself can be programmed on the board with all the I/O system, which save money and give benefits particularly to beginner in microcontroller programming. This new microcontroller of MCS51 family is marked with a letter ‘S’ in the middle of it’s type, AT89S51 and AT89S52. The software used in this project is EASEMicro51 ver 1.1, compiled by himself, that implement an In System Programming through PC parallel port. In System Programmable be able to program microcontroller using PC. In design the circuit, component can connected to each other using wire-wrapping technique. This technique is always used in protaip system before the product revenue in large amount. For beginner, hopefully this thesis can help you to explore more on microcontroller MCS51 family in the cheapest way.